Association of nutrient intake and body mass index among women diagnosed with Polycystic Ovary Syndrome (PCOS) - Yumaizar Fitria; Etika Ratna Noer (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Polycystic Ovary Syndrome (PCOS) is a prevalent hormonal disorder affecting women of reproductive age, frequently linked to overweight and obesity. This condition can elevate the risk of metabolic complications and infertility; therefore, early intervention through nutritional strategies is crucial.This study aimed to examine the association between dietary intake and body mass index (BMI) in women diagnosed with PCOS. A cross-sectional design was used, involving 30 participants in Semarang, conducted from September to November 2024. The data on nutrient intake, including energy, carbohydrates, protein and fat, were collected using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Body weight was measured using a digital scale and height was measured with a portable stadiometer (Seca). Data were analyzed using Pearson correlation tests. The results of the study showed a significant correlation between protein, energy, and fat intake and BMI (p<0.01), while the correlation between carbohydrate intake and BMI was not significant (p=0.060). Protein intake had the strongest correlation with BMI (r=0.640) followed by energy (r=0.531), fat (r=0.470) and carbohydrates (r=0.347). The results highlight the significance of macronutrient intake management, especially protein, in weight control for women with PCOS